Avaliação ergonômica da colheita florestal em área com madeira danificada pelo vento - Barbosa, Verilma Amparo (2015)
This study aimed to perform ergonomic analysis of workers in forest harvesting activities in area with wood damaged by wind, for improvement of health, safety, comfort and therefore increased productivity. Data collection was carried out at Fazenda Tronqueiras in the municipality of Virginópolis (Minas Gerais) in November 2014. The study population consisted of nine (9) for men with a mean age of 41 years under the pre mowing activities cutting, felling, delimbing, bucking, extraction and manual loading. In addition to the working conditions were evaluated the biomechanics (the REBA and MICHIGAN methods), the physical workload, the risk of repetitive strain injury / musculoskeletal disorder related to work (RSI / MSDs), the thermal environment at work and the vibration and noise emitted during operation with chainsaw. The workers said they had not received guidance regarding ergonomics and safety. With the analysis of the physical load, all activities exceeded the limit of cardiovascular load, which is 40%. In biomechanics, the values found regarding risks for compression of vertebral disc L5-S1, were above the recommended limits in extraction activities and manual loading. The present study showed that wood forest harvesting damaged by the wind the way it has been performed, exposes workers to eminent ergonomic risks, mainly by adopting inadequate postures, exaggerated forces use, vibration and noises exposure emitted by equipment used in work activities. Therefore both preventive and corrective actions are necessary and efficient to a efficiently work performance and preserving the health and safety of the worker